Coastal Impacts Driven by Sea-Level Rise in Cartagena de Indias - Orejarena-Rondón, Andrés F.; Sayol, Juan M.; Marcos, Marta; Otero, Luis; Restrepo, Juan C.; Hernández-Carrasco, Ismael; Orfila, Alejandro (Frontiers in Marine Science, 2019)
This work analyzes the coastal impacts of the combined effect of extreme waves and sea level extremes, including surges and projected mean sea level rise in Bocagrande, Cartagena (Colombia). Extreme waves are assessed from a wave reanalysis that are propagated from deep waters to the beach considering the hydrodynamic processes and taking into account the interaction between waves and the coastal elevation within the study area. First, we consider present sea level, storm surges and waves affecting the area. Next, we analyze the effect of sea level rise according to a moderate (RCP4.5) climate change scenario for the 21st century (years 2025, 2050, 2075 and 2100). The most pessimistic scenario (year 2100) yields a percentage of flooded area of 97.2%, thus revealing the major threat that represents sea level rise for coastal areas in the Caribbean Sea.